Novel use of the Bakri balloon to minimize empty pelvis syndrome following laparoscopic total pelvic exenteration. (4th September 2020) - Bankar, S.; Desouza, A.; Paliwal, V.; Pandey, D.; Gori, J.; Sukumar, V.; Rohila, J.; Saklani, A.
Abstract: Aim: Pelvic exenteration is the only surgical option for locally advanced pelvic malignancies infiltrating the surrounding organs. The resultant pelvic void after the procedure is responsible for a number of complications, collectively termed empty pelvis syndrome (EPS). We aim to show how EPS can be minimized by presenting a case series demonstrating the surgical technique of laparoscopic total pelvic exenteration with bilateral pelvic node dissection along with a novel use of the Bakri balloon. Method: This is a case series of three successive patients undergoing laparoscopic total pelvic exenteration for locally advanced primary, nonmetastatic rectal adenocarcinoma over a period of 1 month in a specialized colorectal unit at a tertiary cancer centre. The Bakri balloon was deployed in all three patients and retained for variable time intervals postoperatively. Features of EPS were prospectively documented. Results: In the first patient, the Bakri balloon was completely deflated and removed on postoperative day (POD) 5. The patient developed subacute intestinal obstruction which resolved with conservative management by POD 12. In the second and third patients, the Bakri balloon was deflated in a sequential manner, beginning on POD 8, until it was finally removed on POD 11. Neither of these patients had any abdominal complaints. A postoperative CT scan of both these patients showed the small bowel loops clearly above the pelvic inlet. Conclusions: The Bakri balloon is a simple, safe and cost‐effective method to reduce the complications of EPS following laparoscopic total pelvic exenteration. A prospective study is ongoing to objectively quantify the benefits of this technique.